Controlled preparation of nitrogen-doped hierarchical carbon cryogels derived from Phenolic-Based resin and their CO2 adsorption properties. (1st May 2022) - Zhou, Yalan; Luo, Lu; Yan, Wen; Li, Zeliang; Fan, Mizi; Du, Guanben; Zhao, Weigang
Abstract: Nitrogen-doped hierarchical carbon cryogels with good monolithic structure are synthesized from phenol (P), melamine (M), and formaldehyde (F) by sol-gel, freeze-drying, and carbonization process with different molar ratios of F/(P + M). The synthesized cryogels have the characteristics of cost-effective and abundant hierarchical pores. The pore structures, chemical properties, and CO2 adsorption performance of the prepared carbon cryogels are investigated. The results reveal that the PF carbon cryogel without N doping shows poor porosity characteristics, which leads to lower CO2 adsorption performance. For the N -doped PMF carbon cryogels, with the increase in the molar ratio of F/(P + M), the specific surface area and micropore volume decreases from 1160.6 to 874.1 m 2 /g and from 0.47 to 0.35 cm 3 /g, respectively, indicating that a lower formaldehyde content is conducive to the formation of more micropores and higher specific surface area. The carbon cryogel PMF2.0 (F/(P + M) = 2.0) exhibits a CO2 adsorption capacity as high as 5.79 mmol/g, and it also has a high CO2 /N2 adsorption selectivity (13.43) and isosteric adsorption heat (33.06 kJ/mol). Thus, the PMF carbon cryogel exhibits immense potential as an adsorbent for CO2 capture, and its excellent performance is attributed to the synergistic effect of N doping and abundant micropores with appropriate size. Graphical abstract: The present manuscript used phenol and melamine as inexpensive raw materials to fully replace resorcinol, with a more economical freeze-drying process for cost-effective nitrogen-doped monolithic hierarchical carbon cryogel preparation, which is a promising candidate for CO2 capture. Image 1 Highlights: Hierarchical N -doped monolithic carbon cryogels were prepared cost effectively. Specific surface area as high as 1160 m 2 /g was performed by PMF carbon cryogel. CO2 adsorption capacity of PMF sample was increased by 145.5% than that PF sample. High isosteric adsorption heat of PMF carbon cryogel up to 33.06 kJ/mol was obtained.